Pendekatan Bermakna dalam Pembelajaran IPS MI/SD Berbasis Kearifan Lokal - Wardatul Amroh Arsita; Siva Silviani; Oman Farhurohman (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study discusses the meaningful approach in Social Studies (IPS) learning at the elementary level (MI/SD) based on local wisdom as an effort to strengthen students’ understanding, character, and social identity. Meaningful learning emphasizes the connection between academic content and students’ real-life experiences, particularly those rooted in local culture, traditions, and social practices. The integration of local wisdom in IPS learning enables students to comprehend social concepts through familiar contexts, making learning more engaging and sustainable. Various studies indicate that learning models, media, and projects based on local wisdom contribute to increased learning motivation, critical thinking skills, and the internalization of social and cultural values. Furthermore, this approach supports character education by fostering tolerance, empathy, and a sense of cultural identity among students. The findings highlight that meaningful learning based on local wisdom aligns with curriculum development and responds to contemporary educational challenges without neglecting cultural roots. Therefore, the meaningful approach grounded in local wisdom is essential for developing holistic, contextual, and culturally responsive IPS learning in MI/SD.